Can an End-to-End Telesepsis Solution Improve the Severe Sepsis and Septic Shock Management Bundle-1 Metrics for Sepsis Patients Admitted From the Emergency Department to the Hospital?. (7th October 2022) - Gaieski, David F.; Carr, Brendan; Toolan, Melanie; Ciotti, Kimberly; Kidane, Amy; Flaada, Drew; Christina, Joseph; Aggarwal, Rajesh
Abstract : IMPORTANCE: Early detection and treatment for sepsis patients are key components to improving sepsis care delivery and increased The Severe Sepsis and Septic Shock Management Bundle (SEP-1) compliance may correlate with improved outcomes. OBJECTIVES: We assessed the impact of implementing a partially automated end-to-end sepsis solution including electronic medical record-linked automated monitoring, early detection, around-the-clock nurse navigators, and teleconsultation, on SEP-1 compliance in patients with primary sepsis, present at admission, admitted through the emergency department (ER). DESIGN, SETTING AND PARTICIPANTS: After a "surveillance only" training period between September 3, 2020, and October 5, 2020, the automated end-to-end sepsis solution intervention period occurred from October 6, 2020, to January 1, 2021 in five ERs in an academic health system. Patients who screened positive for greater than or equal to 3 sepsis screening criteria (systemic inflammatory response syndrome, quick Sequential Organ Failure Assessment, pulse oximetry), had evidence of infection and acute organ dysfunction, and were receiving treatment consistent with infection or sepsis were included. MAIN OUTCOMES AND MEASURES: SEP-1 compliance during the "surveillance only" period compared to the intervention period. RESULTS: During the intervention period, 56, 713 patients presented to the five ERs; 20, 213 (35.6%) met electronic screening criteria for potential sepsis; 1, 233 patients had a primary diagnosis of sepsis, present at admission, and were captured by the nurse navigators. Median age of the cohort was 68 years (interquartile range, 57–79 yr); 55.3% were male; 63.5% were White/Caucasian, 26.3% Black/African-American; was 16.7%, and 879 patients (71.3%) were presumed bacterial sepsis, nonviral etiology, and SEP-1 bundle eligible. Nurse navigator real-time classification of this group increased from 51.7% during the "surveillance only" period to 71.8% during the intervention period ( p = 0.0002). Five hospital SEP-1 compliance for the period leading into the study period (July 1, 2020–August 31, 2020) was 62% ( p < 0.0001), during the "surveillance only" period, it was 68.4% and during the intervention period it was 78.3% ( p = 0.002). CONCLUSIONS AND RELEVANCE: During an 11-week period of sepsis screening, monitoring, and teleconsultation in 5 EDs, SEP-1 compliance improved significantly compared with institutional SEP-1 reporting metrics and to a "surveillance only" training period.